A high-entropy alloy carbon-nitrogen composite catalytic material, a preparation method thereof and an application thereof

CN122999258APending Publication Date: 2026-10-30UNIV OF ELECTRONICS SCI & TECH OF CHINA
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611507932.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-28
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0004]本发明的目的在于提供一种高熵合金碳氮复合催化材料、改性隔膜及其在锂硫电池中的应用,用于解决现有技术中高熵合金活性位点易团聚失活、结构稳定性不足以及导电性有待提升的技术问题

Benefits of technology

[0026]1、本发明通过在合成过程中引入丝素蛋白,利用其与过渡金属离子的螯合作用将其锚定于金属有机框架中,经高温碳化后显著提高了材料煅烧后的氮掺杂含量,形成大量吡啶氮、吡咯氮等活性位点,进一步增强了对多硫化物的化学亲和力与催化转化能力。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122999258A_ABST
    Figure CN122999258A_ABST
Patent Text Reader

Abstract

The application relates to a high-entropy alloy carbon-nitrogen composite catalytic material and a preparation method and application thereof, and belongs to the technical field of battery diaphragm coating. The high-entropy alloy is composed of Co, Ni, Cu, Mn, Cr and Fe, the polydopamine-derived carbon-nitrogen protection skeleton effectively prevents the high-entropy alloy nanoparticles from agglomerating and growing, provides rich attachment sites for the alloy, the incorporation of silk fibroin significantly improves the nitrogen content of the material after calcination, the hollow thin shell structure effectively shortens the electrolyte permeation path and promotes the rapid migration of lithium ions at the diaphragm interface. When used as a polypropylene diaphragm coating of a lithium-sulfur battery, the material can effectively chemisorb lithium polysulfide and significantly reduce the redox reaction energy barrier of the lithium polysulfide, meanwhile, the graphitized dense carbon-nitrogen skeleton effectively improves the conductivity and promotes ion transmission, thereby effectively inhibiting the shuttle effect, accelerating the reaction kinetics and improving the cycle stability and rate performance of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of battery materials technology, specifically relating to a high-entropy alloy carbon-nitrogen composite catalytic material, its preparation method, and its application. Background Technology

[0002] Energy is the foundation and driving force of human civilization. For a long time, the massive consumption of traditional fossil fuels such as coal, oil, and natural gas has led to increasingly severe ecological and environmental problems, seriously hindering the sustainable development of human society. To address the energy crisis and climate challenges, it is imperative to promote an energy revolution primarily based on renewable energy sources such as solar, wind, and hydropower. Against this backdrop, high-efficiency energy storage technology has become a key link in energy transformation, leading to the widespread application of lithium-ion battery energy storage. However, the energy density of currently mature traditional lithium-ion batteries is gradually approaching its theoretical limit, making it difficult to meet the stringent requirements of future long-range electric transportation and large-scale energy storage systems.

[0003] Lithium-sulfur batteries, using elemental sulfur as the positive electrode and metallic lithium as the negative electrode, possess extremely high theoretical specific capacity (1675 mAh / g) and theoretical energy density (2600 Wh / kg). Sulfur resources are abundant, inexpensive, and environmentally friendly, making them considered the most promising next-generation high-energy-density electrochemical energy storage system after lithium-ion batteries. However, the commercialization of lithium-sulfur batteries is constrained by several key issues, primarily including the poor conductivity of sulfur, the significant volume change due to the density difference between elemental sulfur and discharge end products, and the polysulfide "shuttle effect." These issues severely affect the cycle stability and lifespan of the batteries. To address these problems, separator modification has attracted considerable attention due to its ability to maintain existing battery assembly processes, controllable costs, and significant effects. While commercially available polypropylene separators possess good electronic insulation, ion permeability, and high chemical stability and mechanical strength, they cannot prevent polysulfides from migrating through the separator to the lithium negative electrode side, thus triggering the "shuttle effect," and they also lack the ability to promote the catalytic conversion of polysulfides. Summary of the Invention

[0004] The purpose of this invention is to provide a high-entropy alloy carbon-nitrogen composite catalytic material, a modified membrane, and its application in lithium-sulfur batteries, in order to solve the technical problems of easy agglomeration and deactivation of active sites, insufficient structural stability, and the need to improve conductivity in existing high-entropy alloys.

[0005] To achieve the above objectives, the present invention adopts the following technical solution:

[0006] One objective of this invention is to provide a high-entropy alloy carbon-nitrogen composite catalytic material, the material having a hollow thin-shell structure, comprising a carbon-nitrogen framework and a high-entropy alloy supported in the carbon-nitrogen framework; the carbon-nitrogen framework is composed of nitrogen-doped carbon derived from silk fibroin and a carbon-nitrogen layer derived from polydopamine; the high-entropy alloy is composed of six metallic elements: Co, Ni, Cu, Mn, Cr, and Fe, with the content ratio of each transition metal active component being 1:1:1:1:1:5, and has a face-centered cubic structure.

[0007] The second objective of the invention is to provide a method for preparing the catalytic material, comprising the following steps:

[0008] S1. Dissolve MnCl2·4H2O, CoCl2·6H2O, NiCl2·6H2O, CuCl2·2H2O, and CrCl3·6H2O in deionized water to prepare a mixed metal salt solution A; dissolve silk fibroin in deionized water to prepare silk fibroin solution B; dissolve K3[Fe(CN)6] and trisodium citrate in deionized water to prepare ferricyanide solution C.

[0009] S2. A mixed solution of metal salts A, silk fibroin solution B, and ferricyanide solution C were heated separately. Then, solutions A and B were added dropwise to solution C, and the mixture was heated and stirred to carry out a co-precipitation reaction. After standing, the solid product was collected by centrifugation, washed with ethanol and deionized water, and freeze-dried to obtain the silk fibroin-doped high-entropy Prussian blue analog precursor SF@HE-PBA.

[0010] S3. Disperse the SF@HE-PBA precursor in Tris buffer solution, add dopamine hydrochloride, stir the reaction at room temperature, centrifuge to separate the solid product, wash with deionized water, and dry to obtain polydopamine-coated silk fibroin doped high-entropy Prussian blue analog precursor SF@HE-PBA@PDA.

[0011] S4. The SF@HE-PBA@PDA precursor was placed in a tube furnace and subjected to a two-step high-temperature annealing treatment under an inert atmosphere. After natural cooling to room temperature, the lithium-sulfur battery separator coating material HE-NC@NC was obtained.

[0012] Preferably, in S1, the molar ratio of K3[Fe(CN)6] to CrCl3·6H2O, CuCl2·2H2O, CoCl2·6H2O, NiCl2·6H2O, and MnCl2·4H2O is 5:1:1:1:1:1; the molar ratio of trisodium citrate to K3[Fe(CN)6] is (11~15):(5~8). The volume ratio of silk fibroin to all deionized water solutions is (40~50) g:(200~250) mL.

[0013] Preferably, in step S2, solution B is added to solution A, stirred for 10 minutes and heated to 40-45°C, then added dropwise to solution C at a rate of 0.1-0.5 mL / s, and stirred at 800-1000 rpm for 12 hours at 40-45°C.

[0014] Preferably, in step S2, ethanol and the reaction solution are added to a centrifuge tube at a volume ratio of 3:1, centrifuged at a speed of (8000~9000) rpm for (3~5) min, washed three times alternately with deionized water and ethanol, and dried under vacuum at (-20~-30) ℃.

[0015] Preferably, in step S3, 400-500 mg of SF@HE-PBA is added to 50 mL of a protective solution with a volume ratio of 1:1 of ethanol to deionized water, and sonicated at 30-50 kHz at 20-30 °C for 30-40 min. Then, the protective solution is added to a Tris buffer solution with a pH of 8.0-9.0, and the volume ratio of the protective solution to the Tris buffer solution is 50 mg:(100-150) mL.

[0016] Preferably, the mass ratio of dopamine hydrochloride to SF@HE-PBA in S3 is (0.4~0.5):1.

[0017] Preferably, the inert atmosphere in step S4 is nitrogen or argon, and the temperature is increased to 300-350℃ at a heating rate of 2-5℃ / min and kept at that temperature for 2 hours, and then increased to 900-950℃ at a heating rate of 2-5℃ / min and kept at that temperature for 2 hours.

[0018] The third objective of this invention is to provide an application of a high-entropy alloy carbon-nitrogen composite catalyst as a membrane modifier in lithium-sulfur batteries. The preparation of a polypropylene membrane coating for lithium-sulfur batteries includes the following steps:

[0019] The catalyst, conductive agent, and binder are uniformly dispersed in a solvent. After the mixture is stirred evenly, it is coated onto the surface of the separator with a scraper and then dried in an oven. After drying, it is quickly transferred to a glove box and cut into circles to obtain the modified lithium-sulfur battery separator.

[0020] Preferably, the base membrane is a polypropylene membrane, a polyethylene membrane, or a polypropylene / polyethylene composite membrane, and the mixed slurry is composed of a catalyst, conductive carbon black, and binder in a mass ratio of (6-9):(1-3):(0.5-2).

[0021] Preferably, the scraper is an adjustable height scraper with a film thickness of 50-100 μm.

[0022] Preferably, the drying oven is set at a drying temperature of 40-100 ℃ and a drying time of 6-24 h.

[0023] Preferably, the diameter of the cut circle is 19mm, and the storage and cutting should be done in a glove box.

[0024] The preparation method of lithium-sulfur battery includes assembling a lithium-sulfur battery modified separator with a Li metal anode, a carbon-sulfur cathode pad, and a carbon sheet to obtain a lithium-sulfur battery.

[0025] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are:

[0026] 1. This invention introduces silk fibroin into the synthesis process and anchors it in the metal-organic framework by chelating it with transition metal ions. After high-temperature carbonization, the nitrogen doping content of the material after calcination is significantly increased, forming a large number of active sites such as pyridine nitrogen and pyrrole nitrogen, which further enhances the chemical affinity and catalytic conversion ability of polysulfides.

[0027] 2. The high-entropy alloy in this invention is composed of six transition metal elements: Co, Ni, Cu, Mn, Cr, and Fe. The synergistic effect among these elements endows the material with abundant catalytic active sites. Through the synergistic catalysis of the high-entropy alloy's multi-metal components, strong chemisorption and efficient bidirectional conversion of polysulfides are achieved, significantly suppressing the shuttle effect and accelerating reaction kinetics. Utilizing the intrinsic high structural stability of the high-entropy alloy and the protective synergy of the Prussian blue analogue-derived carbon-nitrogen framework, long-term retention of active sites and a significant improvement in battery cycle stability are achieved. Simultaneously, the synergistic conductive network with the graphitized carbon-nitrogen framework constructs efficient electron and ion fast transport channels, comprehensively improving the battery's rate performance and active material utilization rate.

[0028] 3. This invention utilizes in-situ self-polymerization of polydopamine on the surface of the precursor, followed by high-temperature carbonization to form a dense and stable carbon-nitrogen protective shell. This protective shell, in synergistic catalysis with the high-entropy alloy, achieves strong chemisorption and efficient bidirectional conversion of polysulfides, significantly suppressing the shuttle effect and accelerating reaction kinetics. Simultaneously, it effectively protects the active sites of the high-entropy alloy, significantly improving the structural stability and cycle durability of the material. Furthermore, the carbon network co-derived with silk fibroin synergistically constructs a continuous three-dimensional rapid electron transport channel, effectively reducing the interfacial charge transfer impedance of the electrode system. Attached Figure Description

[0029] Figure 1 This is a scanning electron microscope image of the HE-NC@NC material prepared in Example 1.

[0030] Figure 2 The image shows a scanning electron microscope image of the HE-NC material prepared in Comparative Example 1.

[0031] Figure 3The results of X-ray absorption fine structure testing of the HE-NC@NC material prepared in Example 1 are shown.

[0032] Figure 4 The graph shows the cycle performance of the lithium-sulfur battery modified separator assembled batteries prepared in Example 1 and Comparative Example 1. Detailed Implementation

[0033] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0034] Example 1

[0035] S1. Add 4.4 mol of K3[Fe(CN)6] and 8.4 mol of trisodium citrate to 90 mL of deionized water and stir until completely dissolved to prepare ferricyanide solution C; Dissolve 0.88 mol each of CrCl3·6H2O, CuCl2·2H2O, CoCl2·6H2O, NiCl2·6H2O, and MnCl2·4H2O in 90 mL of deionized water and stir until completely dissolved to prepare metal salt mixed solution A; Dissolve 40 mg of silk fibroin in 20 mL of deionized water and stir until completely dissolved, and record this as silk fibroin solution B;

[0036] S2. Add silk fibroin solution B to the prepared metal salt mixed solution A and stir for 10 min to obtain a mixed solution. Then heat the mixed solution and ferricyanide solution C to 45℃. Add the mixed solution dropwise to the ferricyanide solution C at a rate of 0.1 mL / s, maintaining the solution temperature at 45℃ and stirring at 1000 rpm for 12 h. After stirring, maintain the temperature at 25℃ and let it stand for 24 h. Add the settled solution and ethanol at a volume ratio of 1:3 to a centrifuge tube, centrifuge at 8500 rpm for 3 min, and filter to collect the solid. Wash the solid product alternately with ethanol and deionized water, and freeze-dry to obtain the silk fibroin-doped high-entropy Prussian blue analog precursor, denoted as SF@HE-PBA-0.2;

[0037] S3. Add 400 mg of SF@HE-PBA-0.2 to a protective solution obtained by mixing 25 mL of deionized water and 25 mL of ethanol. Sonicate at 20 °C for 30 min, then add 150 mL of Tris buffer with a pH of 8.5 and stir at 500 rpm for 10 min to obtain solution D. Add 160 mg of dopamine hydrochloride to 20 mL of deionized water and stir until completely dissolved to obtain solution E. Quickly pour solution E into solution D, stir at 800 rpm for 6 h at room temperature and let stand for 24 h. Centrifuge at 8500 rpm for 10 min, filter to collect the solid, wash the solid product alternately with ethanol and deionized water, and freeze-dry to obtain the polydopamine-coated silk fibroin-doped high-entropy Prussian blue analog precursor, denoted as SF@HE-PBA-0.2@PDA;

[0038] S4. Take 400 mg of SF@HE-PBA-0.2@PDA and place it in a tube furnace. In a nitrogen atmosphere, first heat the mixture to 350℃ at a heating rate of 2℃ / min and react at that temperature for 2 hours. Then heat the mixture to 950℃ at a heating rate of 2℃ / min and react at that temperature for 2 hours. Cool the mixture to room temperature and record it as HE-NC-0.2@NC.

[0039] This embodiment describes the application and testing of HE-NC-0.2@NC material as a membrane modification material.

[0040] Weigh 70 mg of HE-NC-0.2@NC material, 20 mg of Super P conductive agent, and 10 mg of polyvinylidene fluoride binder, and add them together to a container containing 500 μL of N-methyl-2-pyrrolidone solvent. Stir continuously until a uniform, viscous black casting solution is formed. Use an automated coating machine to uniformly coat the casting solution onto the surface of a commercial polypropylene separator, forming a liquid film with a thickness of 100 μm. Then, transfer the coated separator to a 60°C oven and dry for 12 hours. Finally, quickly transfer the dried separator to a glove box and use a die-cutting machine to cut the dried modified separator into circular films with a diameter of 19 mm for later use.

[0041] Example 2

[0042] S1. Add 4 mol of K3[Fe(CN)6] and 8 mol of trisodium citrate to 90 mL of deionized water and stir until completely dissolved. This solution is called ferricyanide solution C. Dissolve 0.8 mol each of CrCl3·6H2O, CuCl2·2H2O, CoCl2·6H2O, NiCl2·6H2O, and MnCl2·4H2O in 90 mL of deionized water and stir until completely dissolved. This solution is called metal salt mixed solution A. Dissolve 80 mg of silk fibroin in 20 mL of deionized water and stir until completely dissolved. This solution is called silk fibroin solution B.

[0043] S2. Add silk fibroin solution B to metal salt mixed solution A and stir for 10 min to obtain a mixture. Then heat the mixture and ferricyanide solution C to 45℃. Add the mixture dropwise to ferricyanide solution C at a rate of 0.1 mL / s, maintaining the solution temperature at 45℃ while stirring at 1000 rpm for 12 h. After stirring, maintain the temperature at 25℃ and let it stand for 24 h. Add the settled solution and ethanol at a volume ratio of 1:3 to a centrifuge tube, centrifuge at 8500 rpm for 3 min, and filter to collect the solid. Wash the solid product alternately with ethanol and deionized water, freeze-dry, and label it SF@HE-PBA-0.4;

[0044] S3. Add 400 mg of SF@HE-PBA-0.4 to a protective solution obtained by mixing 25 mL of deionized water and 25 mL of ethanol. Sonicate at 20 °C for 30 min, then add 150 mL of Tris buffer with a pH of 8.5 and stir at 500 rpm for 10 min to obtain solution D. Add 160 mg of dopamine hydrochloride to 20 mL of deionized water and stir until completely dissolved to obtain solution E. Quickly pour solution E into solution D, stir at 800 rpm for 6 h at room temperature, and let stand for 24 h. Centrifuge at 8500 rpm for 10 min, filter to collect the solid, wash the solid product alternately with ethanol and deionized water, freeze-dry, and label as SF@HE-PBA-0.4@PDA;

[0045] S4. Take 400 mg of SF@HE-PBA-0.4@PDA and place it in a tube furnace. In a nitrogen atmosphere, first heat the mixture to 350℃ at a heating rate of 2℃ / min and react at that temperature for 2 hours. Then heat the mixture to 950℃ at a heating rate of 2℃ / min and react at that temperature for 2 hours. Cool the mixture to room temperature and record it as HE-NC-0.4@NC.

[0046] This embodiment describes the application and testing of HE-NC-0.4@NC material as a membrane modification material.

[0047] Weigh 70 mg of HE-NC-0.4@NC material, 20 mg of Super P conductive agent, and 10 mg of polyvinylidene fluoride binder, and add them together to a container containing 500 μL of N-methyl-2-pyrrolidone solvent. Stir continuously until a uniform, viscous black casting solution is formed. Use an automated coating machine to uniformly coat the casting solution onto the surface of a commercial polypropylene separator, forming a liquid film with a thickness of 100 μm. Then, transfer the coated separator to a 60°C oven and dry for 12 hours. Finally, quickly transfer the dried separator to a glove box and use a die-cutting machine to cut the dried modified separator into circular films with a diameter of 19 mm for later use.

[0048] Comparative Example 1

[0049] The difference between Comparative Example 1 and Example 1 is that step S3 is omitted, while the other steps remain unchanged to obtain HE-NC. The modified diaphragm is prepared in the same manner as in Example 1.

[0050] Comparative Example 2

[0051] The difference between Comparative Example 1 and Example 1 is that in step S1, solution B is prepared by dissolving 1.1 mol each of CuCl2·2H2O, CoCl2·6H2O, NiCl2·6H2O, and MnCl2·4H2O in 90 mL of deionized water and stirring until completely dissolved. This solution is recorded as solution B. All other steps remain unchanged to prepare HE(CoNiCuMnFe)-NC. The modified membrane preparation is the same as in Example 1.

[0052] The materials described in Example 1 and Comparative Example 1 were characterized using scanning electron microscopy, and the test results are as follows: Figure 1 and Figure 2 As shown, the HE-NC-0.2@NC material exhibits a regular cubic shape with a particle size of approximately 300 nm, while HE-NC collapses into a spherical shape. The polydopamine layer protects the regular polyhedral structure of PBA from being destroyed during the carbonization process.

[0053] The crystal form of the material in Example 1 was characterized using X-ray diffraction (XRD), such as... Figure 3 As shown, the XRD pattern shows only three characteristic peaks at 43.4°, 50.6° and 74.4°, which correspond to the (111), (200) and (220) crystal planes of the face-centered cubic structure, respectively, proving the formation of a high-entropy alloy and graphitized carbon.

[0054] At a current density of 0.2 C, the long-cycle performance of Comparative Examples 1 and 2 and Examples 1 and 2 was tested, and the test results are as follows: Figure 4 As shown, the HE-NC-0.2@NC material exhibits better battery performance, with an initial specific capacity of 1266.51 mAh / g. After 100 charge-discharge cycles, it retains 1085.83 mAh / g, with a capacity retention rate of 84.91%, and the coulombic efficiency remains consistently above 99%.

[0055] The preferred embodiments of the present invention disclosed above are merely illustrative of the invention. These preferred embodiments do not exhaustively describe all details, nor do they limit the invention to specific implementations. Clearly, many modifications and variations can be made based on the content of this specification. This specification selects and specifically describes these embodiments to better explain the principles and practical applications of the invention, thereby enabling those skilled in the art to better understand and utilize the invention. The invention is limited only by the claims and their full scope and equivalents.

Claims

1. A method for preparing a high-entropy alloy carbon-nitrogen composite catalytic material, characterized in that, Includes the following steps: S1. Dissolve Cr salt, Cu salt, Co salt, Ni salt, and Mn salt in deionized water to prepare a mixed metal salt solution A; dissolve silk fibroin in deionized water to prepare silk fibroin solution B; dissolve K3[Fe(CN)6] and trisodium citrate in deionized water to prepare ferricyanide solution C. S2. Add silk fibroin solution B to metal salt mixed solution A to obtain a mixed solution; heat the mixed solution and ferricyanide solution C to 45°C, add the mixed solution dropwise to ferricyanide solution C, and carry out a co-precipitation reaction by heating and stirring; after standing, centrifuge to collect the solid product, wash with ethanol and deionized water, and freeze-dry to obtain the silk fibroin-doped high-entropy Prussian blue analog precursor SF@HE-PBA; S3. Disperse SF@HE-PBA in Tris buffer solution, add dopamine hydrochloride, stir the reaction at room temperature, centrifuge to separate the solid product, wash with deionized water, and dry to obtain polydopamine-coated silk fibroin doped high-entropy Prussian blue analog precursor SF@HE-PBA@PDA. S4. Place SF@HE-PBA@PDA in a tube furnace and perform a two-step high-temperature annealing treatment under an inert atmosphere. Then, allow it to cool naturally to room temperature to obtain a high-entropy alloy carbon-nitrogen composite catalyst.

2. The method for preparing a high-entropy alloy carbon-nitrogen composite catalytic material according to claim 1, characterized in that, In S1, the Cr salt, Cu salt, Co salt, Ni salt, and Mn salt are CrCl3·6H2O, CuCl2·2H2O, CoCl2·6H2O, NiCl2·6H2O, and MnCl2·4H2O, respectively.

3. The method for preparing a high-entropy alloy carbon-nitrogen composite catalytic material according to claim 2, characterized in that, In S1, the molar ratio of K3[Fe(CN)6] to CrCl3·6H2O, CuCl2·2H2O, CoCl2·6H2O, NiCl2·6H2O, and MnCl2·4H2O is 5:1:1:1:1:1; The molar ratio of trisodium citrate to K3[Fe(CN)6] is 11~15:5~8; The ratio of the total amount of deionized water used in the mixed solution A of silk fibroin and metal salt, silk fibroin solution B, and ferricyanide solution C is 40~100mg:200~250mL.

4. The method for preparing a high-entropy alloy carbon-nitrogen composite catalytic material according to claim 2, characterized in that, In step S2, silk fibroin solution B is added to the prepared metal salt mixed solution A, stirred for 10 min and heated to 40-45°C, and then added dropwise to ferricyanide solution C at a rate of 0.1-0.5 mL / s. The mixture is stirred at 800-1000 rpm for 12 h at 40-45°C.

5. The method for preparing a high-entropy alloy carbon-nitrogen composite catalytic material according to claim 2, characterized in that, In step S2, ethanol and the reaction solution are added to a centrifuge tube at a volume ratio of 3:1, centrifuged at 8000~9000 rpm for 3~5 min, and the solid is collected by filtration. The solid product is washed alternately with ethanol and deionized water and dried under vacuum at -20~-30℃.

6. The method for preparing a high-entropy alloy carbon-nitrogen composite catalytic material according to claim 2, characterized in that, In step S3, 400-500 mg of SF@HE-PBA is added to 50 mL of a protective solution with a volume ratio of 1:1 of ethanol to deionized water. The solution is then sonicated at 20-30°C for 30-40 min. The protective solution is then added to a Tris buffer solution with a pH of 8.0-9.0, with a volume ratio of 50 mg to 100-150 mL.

7. The method for preparing a high-entropy alloy carbon-nitrogen composite catalytic material according to claim 2, characterized in that, In S3, the mass ratio of dopamine hydrochloride to SF@HE-PBA is 0.4~0.5:

1.

8. The method for preparing a high-entropy alloy carbon-nitrogen composite catalytic material according to claim 2, characterized in that, In step S4, the inert atmosphere is nitrogen or argon, and the two-step high-temperature annealing process is as follows: the temperature is increased to 300-350℃ at a heating rate of 2-5℃ / min and kept at a constant temperature for 2 hours, and then the temperature is increased to 900-950℃ at a heating rate of 2-5℃ / min and kept at a constant temperature for 2 hours.

9. A high-entropy alloy carbon-nitrogen composite catalytic material, characterized in that, It is prepared by the preparation method according to any one of claims 1-8.

10. The application of the high-entropy alloy carbon-nitrogen composite catalyst material as described in claim 9 as a membrane modifier in lithium-sulfur batteries.